Structure of the forest ecotone in the Babia Góra Massif, Western Carpathians - Szwagrzyk, Jerzy (IGiPZ PAN, 2015)
The structure of forest stands and tree architecture at the forest ecotone were analysed at the Alpine timberline zone of the Babia Góra massif of the Western Carpathians. Tree stand and tree characteristics displayedlarge differences in various locations. On the north slope of the massif, trees at the timberline grow relatively tall and slender, and have narrow crowns. Trees at the timberline on the south-west facing slopes of the massif,at higher elevations, are shorter, with lower slenderness indices and relatively broader crowns. These results suggest, that different environmental factors play major roles in shaping the structure of the timberline in variouselevations and various exposures.
24 cm
Keywords: Geography